Embryonic development of the southern surf crab Ovalipes trimaculatus (Decapoda: Brachyura: Portunoidea) - Martelli, Antonela (2016)
The embryogenesis of Ovalipes trimaculatus, a member of the highly valued portunid swimming crabs, was studied under nearly constant temperature (13±1°C), salinity (33) and photoperiod (14 h light:10 h dark) conditions. A five-stage scale of embryonic development was defined for the species. Time required to complete development averaged 35.7±2.11 days, showing no significant differences between embryos located in inner, middle and outer portions of the egg mass. The egg chorion was rounded and showed the highest growth in diameter between stages I (morula-blastula-gastrula) and II (primordium of larval structure) and between stages III (appendage formation) and IV (eye formation). Results reported here provide a baseline for optimizing hatchery operations and useful information for management purposes.